Peningkatan Keterampilan Analisis dan Minat Belajar Peserta Didik Melalui Pendekatan TaRL Dan CRT Dengan Model PBL Pada Materi Penyangga - Nabella, Dei Gratia Kanthi; Rinaningsih; Setyawati, Lina Dwi (Jurnal Penelitian Pendidikan IPA, 2023)
Classroom action research was conducted to determine the increased analytical skills and students' interest in 2 cycles. Learning is carried out by applying the Problem-Based Learning (PBL) model with the Culturally Responsive Teaching (CRT) and Teaching at The Right Level (TaRL) approaches. Learning is carried out referring to the Kurikulum Merdeka. The research carried out was of the type of classroom action research. The research subjects were 26 students from the same class and school. The research was carried out in two cycles. The first cycle carried out learning using the PBL model with a CRT approach. The same learning was carried out in the second cycle using the TaRL approach. Data collection techniques are obtained from students' pre-tests and post-tests on students' analytical skills and learning interests. The research method is quantitative and descriptive qualitative, with an analysis technique using N-Gain and categorized based on the Likert scale. Research shows an increase in students' analytical skills to 0.46 or in the medium category. The classical increase in students' learning interest is as much as 95% in the high category.